Evaluation of Lactation Promotion as Part of Baby Friendly Hospital - Arsani Lailatul Inayah; Lina Handayani; Azidanti Saufi (Intelektual Pustaka Media Utama, 2017)
Decrease of maternal and infant mortality as well as increasing of the exclusive breastfeeding are major public health priorities in Indonesia. In decreasing the maternal and infant mortality, the government developed a program for the community as Baby Friendly Hospital (BFH) to prevent the effects, to support, and to promote breastfeeding. PKU Muhammadiyah hospital in Yogyakarta was one of the BFH program managers. The purpose of this study was to determine the breastfeeding promotion activities as part of BFH at PKU Muhammadiyah Hospital in Yogyakarta.This was a qualitative descriptive study. The findings of this study were inputs consisting of 1) the knowledge and skills to better convey information indicates the quality of human resources. 2) promotion of the policies for all workers to reach the goal. 3) financial promotion is supported by the operating system in the hospital. 4) supporting facility to promote lactation leaflets, posters, ANC class, a breastfeeding counselor and nursing areas. Implementation of lactation promotion was conducted in accordance with program planning of BFH.